2014
DOI: 10.1097/scs.0000000000001140
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Fibrin Plays a Role on Healing of Acute-Traumatic Ear Drum Perforation

Abstract: Here we found that PRF is a biomaterial that quickens the healing of ear drum which is autogenous and simply prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 13 publications
1
10
0
2
Order By: Relevance
“…Eventually 24 patients (12 males and 12 females) In Kartush et al study it was determined that patching does not heal perforations with a size of more than 5 mm which is in concordance with the present study 9 . In a similar study by Habesoglu et al 32 patients with acute TM perforation underwent repair with plateletrich fibrin; while no intervention was done for control group 7 . At the end of the first month TM was completely healed in 64% of patients in intervention and 22% of patients in control group which is in agreement with the results of our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually 24 patients (12 males and 12 females) In Kartush et al study it was determined that patching does not heal perforations with a size of more than 5 mm which is in concordance with the present study 9 . In a similar study by Habesoglu et al 32 patients with acute TM perforation underwent repair with plateletrich fibrin; while no intervention was done for control group 7 . At the end of the first month TM was completely healed in 64% of patients in intervention and 22% of patients in control group which is in agreement with the results of our study.…”
Section: Resultsmentioning
confidence: 99%
“…These methods can be used for stable, uninfected and relatively small perforations using gelfoam, hyaluronic acid film (Epidisc) and cigarette paper 2,3 . Previous studies have proposed various materials such as paper patch, hyaluronic acid fat, basic-fibroblast growth factor (b-FGF), platelet-rich fibrin and platelet-rich plasma (PRP) for TM repair with a variety of complications and success rates [4][5][6][7][8] . Thus in the present study we aimed to evaluate the effect of PRPenriched gelfoam on the healing of chronic TM perforation in comparison with gelfoam alone.…”
Section: Introductionmentioning
confidence: 99%
“…the lateral surface of a cartilage graft and TM remnant during myringoplasty. In a comparison with spontaneous healing, Habeşo glu et al [17] reported that the use of PRF in acute traumatic TM perforations provided significantly better healing rates and times. Although few studies have examined the use of PRF for the closure of TM perforations, PRF could become an important method for repairing TM perforations because it contains a high concentration of growth factors and is strong and elastic.…”
Section: Discussionmentioning
confidence: 98%
“…Platelets are discoid and anuclear structures shaped like a lens, 1 to 4 ìm in greatest diameter. The normal level for platelets in a healthy subject is 100,000 to 400,000 per mm 3 . Their lifespan is 3 to 10 days.…”
Section: Discussionmentioning
confidence: 99%
“…Reksoidiputro et al reported that PRF can speed up skin graft healing and increase graft survival in facial plastic and reconstructive surgery 2) . Habesoglu et al found that autogenous PRF quickens the healing of injured ear drums 3) .…”
Section: Introductionmentioning
confidence: 99%